2019
DOI: 10.1371/journal.pone.0220460
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of home blood pressure monitoring among French GPs: A long and winding road

Abstract: BackgroundTo explore the perception of home blood pressure monitoring (HBPM) by general practitioners (GPs) in everyday practice in order to identify facilitators and barriers to its implementation in daily practice.MethodsA qualitative study comprising the conduct of six focus groups between October 2016 and February 2017, gathering 41 general practitioners in primary care practice in Lorraine (North Eastern France), with thematic and comprehensive analysis.ResultsThe first reasons given by GPs to explain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
1
16
0
1
Order By: Relevance
“…In France, a growing number of health professionals are proposing HBPM to their hypertensive patients. 8 We found a positive association between visiting a GP and possessing a HBPM device among those aware of their hypertension. This highlights the importance of health professionals, and especially GP, in the management of this condition.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In France, a growing number of health professionals are proposing HBPM to their hypertensive patients. 8 We found a positive association between visiting a GP and possessing a HBPM device among those aware of their hypertension. This highlights the importance of health professionals, and especially GP, in the management of this condition.…”
Section: Discussionmentioning
confidence: 57%
“…Simply possessing a HBPM device is not enough; it must also be used and data must be shared with medical doctors. 8,28,29 Although participants in the Esteban study were asked about possessing (or not) a HBPM device, no data were collected on whether they used them. This could explain the absence of expected relationships between adherence to treatment and control of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two web-based surveys in the UK confirmed that GPs have become more likely to use HBPM to diagnose hypertension since the introduction of new national guidance in 2011 [ 23 , 24 ]. Some studies also found a wider use of HBPM to diagnose hypertension by young GPs, those working in groups or MHC, and clinical tutors [ 10 , 12 ]. These are probably important factors in the promotion of HBPM.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, there are no data available on the practice of HBPM for the Auvergne region. The barriers to the use of HBPM are numerous, but the cost of the device and non-reimbursement seem to be an important one [ 8 , 12 ]. Since 2013, the French National Health Insurance Body (FNHIB) has taken measures to promote the use of HBPM among General practitioners (GPs).…”
Section: Introductionmentioning
confidence: 99%